B201 Cranial nerve VI palsy after spinal anesthesia – a case report. (11th August 2022) - Katerenchuk, V; Calçada, A; Rodrigues, L; Capelão, A; Ferreira, I
Abstract : Background and Aims: Cranial nerve (CN) VI palsy following spinal anesthesia is a rare complication. The aim of this case report is to highlight this unusual injury to promote an adequate diagnosis and management. Methods: Patient written consent was obtained. Results: The authors describe the case of a 21-year-old healthy male patient scheduled for excision of a sacrococcygeal pilonidal sinus. Surgery was performed under spinal anesthesia, with multiple attempts at dural puncture with a 27G Whitacre and 25G Quincke spinal needles. Anesthesia and surgery were uneventful with same-day discharge. On postoperative day 1, the patient developed occipital postural headache and a diagnosis of post dural puncture headache (PDPH) was made. Symptoms subsided within 8 days of conservative treatment. On postoperative day 11, the patient returned to the emergency department with complains of blurred and double vision. Neurological examination was performed and a diagnosis of cranial nerve VI compression neuropathy was postulated. Occlusion therapy was prescribed and symptoms ceased by day 17 postoperatively. Conclusions: If CN VI palsy is an isolated neurologic deficit occurring within 3 weeks of dural puncture and preceded by a PDPH, it is likely a consequence of dural puncture leading to intracranial hypotension and CN traction. 1 Conservative treatment is generally adequate to minimize patients' discomfort and further investigation unwarranted if the deficit resolves spontaneously. It is important for anesthesiologists to be aware of this injury, to inquire about ocular symptoms and to educate patients and peers concerning this rare complication which can manifest within several days after postoperative discharge.